PENGGUNAAN CAMPUR KODE DALAM ACARA “CATATAN NAJWA BERSAMA MAUDY AYUNDA” DI MEDIA SOSIAL YOUTUBE - Ginting, Nismara Aulina; Efrienka, Sity Yorinda; Zamzami, Aulia Rahma (Teks: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2023)
This research was conducted with the aim of describing the form of code mixing and the context of the codes used in the event "Catatan Najwa bersama Maudy Ayunda". This research uses a qualitative descriptive approach. The data collection method used in this study is the listening and recording method with the research instrument in the form of a video in the Catatan Najwa event uploaded by Najwa Shihab to youtube. Data was obtained and collected using the SBLC (Listen Free Folding Record) technique with the note-taking technique as a follow-up to classifying the data. The presentation of the results of the analysis is described in written form. The results showed that there were five forms of code mixing, namely: word form code mixing in English, phrase code mixing in English, baster code mixing in English, clause code mixing in English, and word repetition code mixing in English.